Transformational Leadership in Managing AI-Based Early Childhood Education: A Study in South Sulawesi - Baharuddin Baharuddin; Busra Bumbungan; Mohtar Kamisi; Arif Efendi AS; Uli Nuha; Yunus Busa; M. Hatta (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to analyze the role of transformational leadership in the management of artificial intelligence (AI)-based early childhood education in South Sulawesi. This study used a mixed methods approach and involved 15 administrators and 150 instructors from 30 regional schools. Quantitative data were collected through a questionnaire survey and analyzed using linear regression, while qualitative data were obtained through in-depth interviews and document analysis. The study findings revealed that transformational leadership significantly influenced the success of AI-based education management, with a regression coefficient (β) of 0.75 (p < 0.01). Key factors such as strategic vision, effective communication, teacher capacity development, and organizational support play an important role. However, challenges such as limited infrastructure, inadequate technical training, and inadequate education policies remain. This study contributes to educational management science by demonstrating how transformational leadership can be a strategic driver to overcome implementation barriers and improve technology integration in early childhood education. Practical implications include guiding school leaders in leadership development programs, informing policy formulation to support AI-based learning, and enhancing institutional readiness for educational innovation. Academically, this research enriches the discourse on applying leadership theory in the context of technological transformation in education.